Forecasting of Total Stock Raw Materials of Double Exponential Smoothing Method (study: PT. Charoen Pokphand Indonesia) - Rani Purbaningtyas; Rahmawati Febrifyaning Tias; M. ZAINAL ABIDIN (Fakultas Teknik Universitas Bhayangkara, 2019)
Inventory control at a company is very important in determining the efficiency of warehouse functions. Uncertain information about the availability of goods in the warehouse affects the decision to be taken in determining the amount of ordering goods. So that it has difficulty in predicting stock in the next month. The negative effect in the future if one predicts the stock will experience excessive stock build up. This study aims to create an application that can help facilitate and maximize the performance of warehouse administration employees in predicting the number of goods that must be ordered for the next period. Forecasting method used is the double exponential smoothing method. This method requires data information in previous years so that in this study took data 4 years earlier. With this forecasting method the forecasting results are obtained close to the actual data. From the results of testing the system imposed on 3 data obtained a system accuracy of 60%.